THU0068 Identification and verification of biomarker candidates for monitoring rheumatoid arthritis activity by mass spectrometry. (12th June 2018) - González-Rodríguez, L.; Calamia, V.; Fernández-Puente, P.; Ruiz-Romero, C.; Lourido, L.; Camacho-Encina, M.; Juliá, A.; Fernández-Nebro, A.; Tornero, J.; Marsal, S.; Blanco, F.J.; ,
Abstract : Background: Rheumatoid arthritis (RA) is a long-lasting inflammatory autoimmune disorder that ultimately leads to the destruction of joint architecture. The activity of this disease is measured by the assessment of clinical symptoms. Objectives: To apply a proteomic strategy to find serum biomarkers able to discriminate patients with different RA activities. Methods: To facilitate the complex measurement of serum by proteomics, a simple, fast and reproducible albumin-specific depletion method using ethanol was optimised and applied to the samples employed in this study. 80 samples from the IMID consortium, classified according to the DAS28 score into low activity 40 and high activity 40 were analysed by mass spectrometry. Four independent pools of the high RA activity samples (10 samples per pool) and 4 pools of the low RA activity samples were firstly albumin-depleted, and then the remnant serum proteins were digested and differentially labelled with iTraq 8-plex reagents. Subsequently, the 8 labelled pools were combined and cleaned using StageTips-C18. Finally, the pool mixture was fractionated by HPLC (Zorbax-C18) and the resulting fractions were analysed by nanoLC-MS/MS using MALDI-TOF/TOF, TripleTOF and LTQ-Orbitrap. Results: The mass spectrometry analysis led to the identification of 186 proteins. In this screening step, the abundance of 9 proteins was found to be significantly different between patients with high (H) and low (L) RA activity. Orthogonal experiments, using Western Blot, protein bead arrays and Multiple Reaction Monitoring (MRM) with synthetic heavy-labelled peptides, were conducted in order to verify some of these these biomarker candidates of RA activity. The results obtained from the verification phase, conducted by MRM on 50 samples from the same cohort, show a decrease of Apolipoprotein B (ratio H/L=0.84, p=0.00), Histidine Rich Glycoprotein (ratio H/L=0.86, p=0.01) and Plasma protease C1 inhibitor (ratio H/L=0.84, p=0.02). Furthermore, this verification phase shows also an increase of Haptoglobin (ratio H/L=1.34, p=0.01) and Serum Amyloid A1 (ratio H/L=1.64, p=0.05), in accordance with that observed in the screening. These proteins are related with the RA process and the effects caused by this type of disease (inflammation and immune disorder in joints). Conclusions: In this proteomic study, 5 proteins were found to be quantitatively altered between patients with high and low RA activity using shotgun and targeted mass spectrometry. Disclosure of Interest: None declared